1990
DOI: 10.1021/ja00169a013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrazines: new charge-transfer physical quenchers of singlet oxygen

Abstract: The rates of reaction of singlet oxygen with 25 hydrazines were determined by following the emission of singlet oxygen at 1270 nm as a function of time. These data are utilized to discuss various options for the quenching mechanism including electron transfer, electronic to vibrational energy transfer, and a contact charge-transfer process.It is now well established that singlet oxygen is responsible for photodynamic destruction of both biologically and commercially important molecules. As a consequence, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 0 publications
5
43
0
Order By: Relevance
“…From the comparison of the traces, it is clear that in general, there is a poor singlet oxygen production for all the systems in which CDs are present, in agreement with our previous results . This low singlet oxygen production can be attributable both to the 1 O 2 quenching process by OH moieties of ethanol and cyclodextrins , and to the PS triplet state quenching caused by the presence of Chl a aggregated forms, as evidenced by the Chl a triplet spectra shown in the inset of Fig. .…”
Section: Resultssupporting
confidence: 89%
“…From the comparison of the traces, it is clear that in general, there is a poor singlet oxygen production for all the systems in which CDs are present, in agreement with our previous results . This low singlet oxygen production can be attributable both to the 1 O 2 quenching process by OH moieties of ethanol and cyclodextrins , and to the PS triplet state quenching caused by the presence of Chl a aggregated forms, as evidenced by the Chl a triplet spectra shown in the inset of Fig. .…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, a saddle point which connects 7 and 4 has been located, but it is too high (27.3 kcal mol −1 ) for ring closure at experimentally relevant conditions. Interaction of singlet oxygen with the nitrogen atoms of 1 is likely lead to a physical quenching process, as has been detected with hydrazines , but such a quenching channel that includes a charge‐transfer interaction was not modeled.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of solvent on singlet-oxygen quenching constants. Previous studies have shown that the singlet-oxygen quenching constants for various amines, hydrazines and iodide ion are smaller in solvents with high values on the ␣ scale (11,(20)(21)(22). This is because amines, hydrazines and iodide ion are easily protonated.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of solvent on the quenching of singlet oxygen by other types of molecules, such as amines, has been analyzed using the solvatochromic parameters of Kamlet, Abboud, Abraham and Taft (18)(19)(20)(21)(22). Typically, three scales are used to gain insight into the mechanism of quenching.…”
Section: Rtmentioning
confidence: 99%